2004
DOI: 10.1088/1126-6708/2004/05/077
|View full text |Cite
|
Sign up to set email alerts
|

Seiberg-Witten Map for Superfields onN=(1/2,0) andN=(1/2,1/2) Deformed Superspace

Abstract: In this paper we construct the Seiberg-Witten maps for superfields on the θ − θ deformed superspaces with N = ( 1 2 , 0) and N = ( 1 2 , 1 2 ) supersymmety. We show that on the N = ( 1 2 , 0) deformed superspace there is no SeibergWitten map for antichiral superfields which is at the same time antichiral, local and which preserves the N = ( 1 2 , 0) supersymmetry. Solutions which break this requirements are presented. On the N = ( 1 2 , 1 2 ) deformed superspace we show that for the chiral gauge parameter, and… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2004
2004
2007
2007

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 61 publications
(96 reference statements)
0
12
0
Order By: Relevance
“…If we consider string theories in the R-R field strength or graviphoton background, coordinates of superspace become non(anti)commutative [3,4,5]. Various aspects of noncommutative superspace have been studied in [6,7,8,9,10,11,12,13,14,15,16,18,19,20,21,22]. Some studies from the viewpoint of supermatrix models are found in [23,24,25].…”
Section: Introductionmentioning
confidence: 99%
“…If we consider string theories in the R-R field strength or graviphoton background, coordinates of superspace become non(anti)commutative [3,4,5]. Various aspects of noncommutative superspace have been studied in [6,7,8,9,10,11,12,13,14,15,16,18,19,20,21,22]. Some studies from the viewpoint of supermatrix models are found in [23,24,25].…”
Section: Introductionmentioning
confidence: 99%
“…We now determine what choice of A and B will preserve the reality of V while concurrently embedding (36). To the first order in C, we find under the above redefinitions that (31) becomes,…”
Section: Gauge Transformationsmentioning
confidence: 99%
“…As we will explicitly show, this is a generalization of SW map to non-anticommutative superspace. Generalizations of SW map to C deformed superspace are studied in [25] and [26]. It is also studied in harmonic superspace [27], [28].…”
Section: Introductionmentioning
confidence: 99%